Safety requirements for the design of collaborative robotic workstations in europe – a review - Faria, Carlos (2020)
Industrial manufacturing is moving towards flexible and intelligent processes. Human-Robot Collaboration (HRC) has a pivotal role in smart factories due to a more versatile resource allocation that ultimately drives higher productivity and efficiency. The physical barriers that separate robots’ and humans’ workspaces are removed to facilitate HRC, which raises new safety concerns. To cope with this new robotics paradigm, regulatory legislation and international safety standards have been issued and are enforced for any machinery placed in factories. In this paper, we aim to shorten the gap between research projects and industry-ready robotic systems, by providing the guidelines and general requirements for collaborative robotic applications. We review the current international safety standards, certification procedures under the scope of European jurisdiction, and elaborate a literature review of papers related to safety for collaborative workstations.